Точні оцінки колмогоровських поперечників класів аналітичних функцій. I - Боденчук, В.В.; Сердюк, А.С. (Український математичний журнал, 2015)
Установлено, что ядра аналитических функций вида удовлетворяют введенному Кушпелем условию C,2n, начиная с некоторого номера nh, который в явном виде выражается через параметр h гладкости ядра. В результате для всех n≥nh получены оценки снизу колмогоровских поперечников d2n в пространстве C функциональных классов, которые представимы свертками ядра Hh,β с функциями φ⊥1, принадлежащими единичному шару пространства L∞. We prove that the kernels of analytic functions of the form satisfy Kushpel’s condition C y,2n starting from a certain number n h explicitly expressed via the parameter h of smoothness of the kernel. As a result, for all n ≥ n h , we establish lower bounds for the Kolmogorov widths d 2n in the space C of functional classes that can be represented in the form of convolutions of the kernel H h,β with functions φ⊥1 from the unit ball in the space L ∞ .